2009
DOI: 10.1161/strokeaha.108.543819
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Quality of Care and Short-Term Mortality Among Patients With Acute Stroke in Denmark

Abstract: Background and Purpose-Sex may predict level of care and successive outcome among patients with stroke. We examined fulfillment of quality of care criteria according to sex and possible impact of any sex-related differences on short-term mortality in a population-based nationwide follow-up study in Denmark. Methods-We identified 29 549 patients admitted with stroke between January 2003 and October 2005 in the Danish National Indicator Project. Data on 30-and 90-day mortality were obtained from The Civil Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 27 publications
5
34
2
1
Order By: Relevance
“…21 Recently, however, studies including large numbers (Ͼ20 000) do report better survival of females as also seen in this study 9,15,22,23 in which gender is significantly associated with 1-year case-fatality. The association was independent of the cardiovascular risk factor variables included in the analysis, indicating that the lower case-fatality rate observed in women 24 is not only a consequence of less frequent occurrence of cardiovascular disease in women.…”
Section: Predictors Of Late Case-fatalitysupporting
confidence: 65%
“…21 Recently, however, studies including large numbers (Ͼ20 000) do report better survival of females as also seen in this study 9,15,22,23 in which gender is significantly associated with 1-year case-fatality. The association was independent of the cardiovascular risk factor variables included in the analysis, indicating that the lower case-fatality rate observed in women 24 is not only a consequence of less frequent occurrence of cardiovascular disease in women.…”
Section: Predictors Of Late Case-fatalitysupporting
confidence: 65%
“…Regarding mortality, the rate was higher for women in the unadjusted analysis, but this difference reversed after multivariate modeling with a higher probability of being alive for women at 3-month follow-up. Although this will remain a controversial issue, such a scenario has also been described by other authors 4,23 and stresses the importance to consider also demographic and clinical aspects besides sex when analyzing stroke mortality rates. Such investigations should also encompass the more complex construct of genderrelated diversity.…”
Section: June 2014mentioning
confidence: 70%
“…Finally, a nationwide study undertaken in Denmark could not link the observed sex-related differences in short-term mortality with differences in acute hospital care. 24 One main problem of the current study, and the reason for the stratified analyses undertaken within different data sets, is the confounding role of disease severity. The so-called confounding by severity, a type of confounding by indication, 25 can arise in observational studies when patients with worse prognosis preferentially receive, or do not receive, a particular treatment on the basis of such prognosis.…”
Section: Discussionmentioning
confidence: 99%